Minería y dependencia: una visión bioarqueológica desde una hacienda mineral de la época virreinal (Perú, siglos XVI-XIX) - Tomasto-Cagigao, Elsa (2024)
The systems of asymmetrical dependency are those of coercive social relations, in which some actors control the actions or access to resources of others, and emic conceptions regarding power, inequality, work, experiences, and emotions are shared. The European invasion of America in the 16th century established a system with these characteristics. This type of relationship was strongly established in the field of metal production. This paper presents some results of a bioarchaeological investigation of a group of skeletons of people buried in a chapel located in a mineral hacienda from the Viceregal period. The impacts on health are analyzed through trauma, malformations, and infections in people of different sex and ancestry. The results show a correlation between the position in the asymmetrical dependency system and the types of fractures, but not with the malformations and infections.